PEMILIHAN STRATEGI PENGADAAN KENDARAAN DINAS PADA PEMERINTAH DAERAH: STUDI ANALISIS NPV DI PEMERINTAH KOTA CILEGON - Sutisna, Nanang (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2025)
Official vehicle procurement is vital to supporting local government operations. The Cilegon City Government faces challenges in choosing an efficient procurement strategy between purchase and lease. This study aims to assess the financial feasibility of both methods using the Net Present Value (NPV) approach over seven years with a 6.88 percent discount rate. Cash flow data include purchasing costs, maintenance, taxes, leasing, fuel, and resale value. The results show that the purchase method yields a less negative NPV than leasing for both echelon II and echelon III vehicles. However, leasing remains relevant for short-term needs and transitional conditions, such as during vehicle replacement processes. Thus, purchase is recommended for long-term use, while leasing is suitable for temporary requirements. These findings are expected to support policy decisions regarding official vehicle procurement in Cilegon